70 Lives saved by laws and regulations that resulted from the bloomberg road safety program. (19th September 2017) - Swedler, David; Miller, Ted; Levy, David
Abstract : The Bloomberg Road Safety Program (BRSP) supports the development of traffic safety laws, regulations, and activities. Six low- and middle-income countries (LMICs) enacted over a dozen such regulations between 2007 and 2013. Purpose: This evaluation estimates the lives saved by these laws in 2007–2013 then projects future reductions in motor vehicle crash (MVC) mortality through 2023. Methods: Local BRSP staff identified traffic laws in Brazil, China, Kenya, Mexico, Turkey, and Vietnam that we categorised as driving while intoxicated, seat belt use, motorcycle-related, and other. To calculate reductions in deaths, we used domestic and international systematic reviews to identify effectiveness of such laws. Discounts in reductions were made for those laws that had poor enforcement, as determined by BRSP staff. Historic MVC deaths saved were estimated using data from the Global Burden of Disease (GBD). Historic growth rates from the GBD were then used to project mortality reductions through 2023. Results: BRSP helped pass laws and regulations that saved an estimated 19 000 lives from 2007–2013. Those laws and regulations will save another 90 000 lives in 2014–2023. Of the 1 09 000 estimated lives likely to be saved, over half will be in China and one-third will be in Vietnam. Limitations for our estimates include use of historic fatality rates; paucity of country-specific intervention publicity, enforcement and effectiveness data; and inherent weaknesses of GBD data. Conclusion: In LMICs, traffic safety interventions associated with the BRSP have the potential to save over 1 00 000 lives from 2007–2023. Significance: Economic analyses can estimate lives saved due to traffic safety regulations in LMICs. Better estimates of local implementation, enforcement, and effectiveness could improve such estimates in the future.